2012
DOI: 10.3747/co.19.1004
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Zoledronic Acid Compared with Clodronate in Multiple Myeloma

Abstract: phd § cost-effective is 80%. Assuming that the benefits of zoledronic acid on pfs and os diminish over 5 years beginning at the end of year 5, the icer is CAN$63,027 per qaly gained. If the benefits of zoledronic acid on pfs and os are assumed to persist for 5 years only, the icer is CAN$76,948 per qaly gained. ConclusionsCompared with clodronate, zoledronic acid represents a cost-effective treatment alternative in patients with multiple myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Many Canadian cost-effectiveness analyses in cancer have been conducted using the utility scores derived from the U.K. tariffs [28][29][30][31] and, to a lesser extent, the U.S. tariffs 32 obtained from the EQ-5D-3L. The implications of this practice of using non-Canadian tariffs have not been determined, and the Canadian Agency for Drugs and Technologies in Health has not yet made an official recommendation on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Many Canadian cost-effectiveness analyses in cancer have been conducted using the utility scores derived from the U.K. tariffs [28][29][30][31] and, to a lesser extent, the U.S. tariffs 32 obtained from the EQ-5D-3L. The implications of this practice of using non-Canadian tariffs have not been determined, and the Canadian Agency for Drugs and Technologies in Health has not yet made an official recommendation on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Brown [25] Len-Dex vs. Dex 2nd line therapy of MM Delea [20] ZOL vs. CLO 1st line therapy of MM Delea [19] ZOL vs. CLO 1st line therapy of MM Garrison [23] MPB vs. MPT vs. MPL vs. MPL-L 1st line therapy of MM transplant-ineligible Grima [22] HCO-HD vs. standard HD MM associated renal failure Hornberger [18] B vs. Dex vs. Len-Dex RRMM Kouroukis [16] ASCT vs. MP 1st line therapy of MM transplant-eligible Mehta [28] B vs. BSC vs. T RRMM Moeller [26] Len-Dex vs. B RRMM Picot [21] B and T based combination therapies with alkylators and steroids 1st line therapy of MM more advanced modeling approaches. Statistical fitting methods allow the extrapolation of the survival results beyond the observed time frame, but rely on assumptions that may differ substantially between different parametric models.…”
Section: Modeling Study Compared Treatment Strategies Indicationmentioning
confidence: 98%
“…Delea and co-authors [19,20] adapted the same model to reflect Canada and the U.K. in order to evaluate the cost-effectiveness of zoledronic acid (ZA) vs. clodronate. Both analyses concluded that using ZA was the most attractive strategy (US$43,065 per QALY gained in Canada.…”
Section: Cost-effectiveness Analysismentioning
confidence: 99%
See 2 more Smart Citations